Impact of anthropogenic pollution on soil properties in and around a town in Eastern India - Sarkar, Arpita; Deb, Shovik; Ghosh, Subhadip; Mandal, Subhadeep; Quazi, Shimona A.; Kushwaha, Amit; Hoque, Anarul; Choudhury, Ashok (Geoderma Regional, 2022)
Urbanization leads to substantial changes in the terrestrial ecosystems. Soils in urban and peri-urban areas are often subject to severe degradation and soil pollution can rise to levels warranting immediate attention. Along with heavy metal contamination and urban waste dumping, occurrence of microplastics in urban soils is a topic of increasing concern in recent years. The present study was conducted in the town of Cooch Behar and its periphery in Eastern India, with the aims to identify the effect of urbanization on soil properties and to quantify the extent of microplastic pollution in a small urban area. Surface soil samples were collected across the town and from its surroundings and analysed for selected soil quality parameters. Quantitative estimation of soil microplastics was performed along with microscopic observation of morphotypes. Assessment of land use-land cover (LULC) status indicated significant increase in urban settlements in 24 years timespan from 1995 to 2019, concurrent with a trend of agricultural intensification around the town during this period. Results showed high soil NO3̶N in some locations and high available P content in the majority of study areas. High Zn (x¯ 1.91 μg g−1), Cu (x¯ 3.36 μg g−1), Cr (x¯ 2.31 μg g−1) and Hg (x¯ 4.69 μg g−1) concentrations were observed while bio-available Cd was found above the critical limit in some places. Soils of some urban and peri-urban locations showed high presence of microplastics (0.2–0.5 or > 0.5 mg g−1). This is one of the first studies of soil contamination and microplastic pollution in small urban settlements (like municipal towns) in India and it indicated the extent of severity due to unmanaged human activities. [Display omitted] •Impact of pollution was observed on soils of an urban and peri-urban area•High NO3̶N and available P was observed in soils•Presence of bio-available Zn, Cu, Cr, Cd and Hg were above critical level•There was microplastic pollution observed•Urbanization affects soil health even in small towns